Avaliação da simetria contralateral na distribuição da doença periodontal em pacientes com periodontites agressiva e crônica - Brito, Liana Freire de (2015)
Symmetry contralateral has been observed in periodontitis. Understanding how periodontal destruction occurs is an important tool for the differential diagnosis of aggressive periodontitis (AG P ) and chronic ( C P). The aim of this comparative cross - sectional study was to evaluate through clinical analysis the existence of a pattern of bilateral periodontal destruction similarity in individuals with AG P and C P . The sample c onsisted of 53 patients with AG P and 39 C P with at least 20 teeth . Probing depth data were recorded (PS) and clinical attachment level (CAL) of the proximal sites (buccal and lingual) incisor teeth, first and second molars. The average values of PS and CAL these sites in patients with AG P were 4.2 ± 2.3 mm 4.9 ± 2.6 mm, respectively. Similarly, in patients with CP were 3.2 ± 1.6 mm and 3.6 ± 2.0 mm. Values of PS and CAL of contralateral sites of the teeth were compared by t t est or Wilcoxon test and correlated by the Pearson and intraclass correlation tests . No differences were f ound between means of PS and CAL for the same number of pairs of sites assessed in patients with AG P and C P. Moderate positive correlations (0.4 - 0.6) to strong (0.7 - 0. 81 ), the two clinical parameters were found between most pairs of contralateral periodontal sites of individuals with A GP , but not with the C P . Suggesting that there is a more symmetrical pattern of periodontal destruction proximal contrala teral sites of individuals with AG P . Individuals with A GP presented more proximal sites with a standard bilateral destruction compared with the C P